Business Process Redesign for Inpatient Installation in Javacare Hospital - Hakim, Audi; Basri, Mursyid Hasan (The Indonesian Journal of Business Administration, 2014)
Abstract - One of Ministry of Health programs that purposed to improve the service quality of hospital services is accreditation program. KARS (Komisi Akreditasi Rumah Sakit) was appointed as an as an independent agency that implementing accreditation of hospitals. Javacare Hospital already accredited by KARS in 2011 and should renew its accreditation in 2014. However, KARS has established new accreditation standards in 2012 with major changes with the previous accreditation standards.  Javacare Hospital should response to the change in KARS accreditation standards and adapts its business to it. Business situation in Javacare Hospital was analyzed based on 5 pillars that influenced its business: customer, environment, people, process, and technology. From business analysis, it was found that there are problems in process and technology pillars in Javacare Hospital. The right way to transform organization is to begin with people and process, then make sure the technology is set up to follow people and process rollout in integrated manner. Based on this consideration, the solution for Javacare Hospital should start with process first, then technology. The proposed solution for Javacare Hospital is to make a documented business process that aligned with the new KARS accreditation standard.  The methodology of the documented business process design takes approach from the methodology of the business process reengineering design. The scope that selected to be designed in this final project is inpatient installation. KARS accreditation standards and hospital minimum service standards (SPM) points were mapped on the business process. Then the business process design was checked by practitioners in Javacare Hospital. There are several steps in this final project’s action plan. The first is to build leader’s commitment because it plays a critical sponsor role to carry out the plans. The second is socialization to ensure those who are affected by change are actively engaged and informed. The third is to perform pilot project before the actual implementation. During the pilot project, there will be several periodic evaluations. Keyword: KARS Accreditation, Business Process, Inpatient Installation, Hospital SPM